Nailfold Videocapillaroscopy in Patients with Rheumatoid Arthritis and Psoriatic Arthropathy on ANTI-TNF-ALPHA Therapy - Daniela Anghel; Carmen Adella Sîrbu; Oana-Georgiana Petrache; Daniela Opriș-Belinski; Maria Magdalena Negru; Violeta-Claudia Bojincă; Cristina Florentina Pleșa; Florentina Ioniță Radu (Diagnostics, 2023)
Videocapillaroscopy is a simple, non-invasive investigation that allows the “in vivo” study of the nailfold capillaries. This method is inexpensive, easily accepted by patients and the results can be easily interpreted. It is mainly used in patients with Raynaud’s phenomenon and systemic sclerosis, but this examination can also be performed on patients who are suspected of having microcirculation alterations, such as rheumatoid arthritis and psoriatic arthritis. It may aid in the diagnosis, evaluation and prognosis of other rheumatic diseases, besides systemic sclerosis. The aim of this study is to identify the nailfold videocapillaroscopic abnormalities in rheumatoid arthritis and psoriatic arthritis patients and analyze the correlation between their evolution and 12 months of anti-TNF-α therapy. The abnormal capillaroscopic findings comprised widened, dilated or giant capillaries and the distortion of the normal nailfold architecture, avascular areas, hemorrhages and neoangiogenesis. Overall, capillary density, dilated capillaries, giant capillaries, elongated capillaries and angiogenesis significantly improved after 12 months. Moreover, no avascular areas were found after 12 months of anti-TNF treatment.